ZAKAZ WYROKOWANIA PONAD ŻĄDANIE STRONY (‘NE EAT IUDEX ULTRA PETITA PARTIUM’) – RZYMSKIE TRADYCJE I WSPÓŁCZESNE REGULACJE POLSKIEGO PROCESOWEGO PRAWA CYWILNEGO - Misztal-Konecka, Joanna (Zeszyty Prawnicze, 2016)
‘NE EAT IUDEX ULTRA PETITA PARTIUM’: THE PROHIBITION ON JUDGEMENTS OVER AND ABOVE THE CLAIM A PARTY HAS LODGED. ROMAN TRADITIONS AND CONTEMPORARY REGULATIONS IN POLISH CIVIL LAW PROCEEDINGS Summary One of the testimonials to the vast influence of Roman law on contemporary civil law, including proceedings, are the Latin legal maxims which have been used for centuries not only by theorists of the law but also by its practitioners. Following the social and political transformation, one of the maxims very often resorted to in Poland is ne eat iudex ultra petita partium. Its importance is confirmed by the fact that it is among the 86 inscriptions decorating the columns in the building of the Polish Supreme Court. This legal maxim is an excerpt from the Roman jurist Iavolenus (D. 10,3,18), who used this expression to rule out the possibility of one of the beneficiaries in an inheritance case obtaining an easement on the testator’s estate for use on his own property which was not part of the estate devised. Clearly the original formulation applied to a different issue than the sense in which it is used nowadays: as a reference to the limitation on a judge’s powers to the subject of the proceedings he is hearing. In the light of the current formulation of Art. 321 of the Polish Code of Civil Procedure a court cannot or rule over and above the claim, or issue a verdict not relating to the claim. This prohibition means that the court cannot issue a verdict other than (aliud) or over and above (super) what the plaintiff or claimant petitioned for. Neither can it rule on any other grounds than those petitioned for by the plaintiff or claimant. The prohibition on judgements over and above the petition applies both to the object of the petition or claim (petitum) as well as to the grounds thereof (causa petendi).